Potential Utilization Of Modified Oil Palm Ash As Filler In Natural Rubber Vulcanizates - Ooi , Zhong Xian (2015)

(untitled)
This work studied the possibility of utilizing oil palm ash (OPA) as filler to reinforce the natural rubber vulcanizates. The OPA loading used in this study was ranged from 0 to 9 phr. The characterization of OPA was carried out prior to compounding by using conventional laboratory-sized two roll mills. Morphological study revealed that the OPA particle was irregular with rough surface and porous structure. The two main mineralogical components in OPA were quartz and calcite which elucidated by Energy dispersive X-ray, X-Ray Fluorescence spectrometry, Fourier transform infrared and X-ray diffraction analysis. Results of the OPA-filled vulcanizates showed that the scorch time and cure time decreased with the incorporation of OPA whereas maximum torque, tensile modulus, and hardness increased. From a reinforcement point’s perspective, it was worthwhile to note that the tensile strength improved by 16 % when 1 phr OPA was incorporated. When compared to the commercial fillers, this OPA-filled vulcanizate showed comparable strength to the 50 phr carbon black-filled vulcanizate and even higher than silica-filled vulcanizate. Besides, the incorporation of low OPA loading has increased the elongation at break whereas silica and carbon black reduced the elongation at break of the natural rubber vulcanizates. The measurement of rubber-filler interaction and morphological studies of tensile fractured surface of OPA, silica, and carbon black-filled natural rubber vulcanizates supported the result obtained from tensile properties. The thermal stability and retention properties after thermal ageing were notably enhanced with the incorporation of OPA and improved as the OPA loading was increased. xxx Thermogravimetric analysis also denoted the thermal stability was depending on the filler loading, thus higher thermal stability was found for higher loading of filler-filled vulcanizates. Last but not least, the effectiveness of three different pre-treatment methods was carried out in order to further improve the tensile strength of the OPA-filled vulcanizates. The pre-treatment media, i.e. cetyltrimethylammonium bromide (CTAB), hydrochloric acid (HCl), and liquid epoxidized natural rubber (LENR) improved the tensile strength of natural rubber vulcanizates. However, other properties such as curing characteristics, elongation at break, hardness, tensile modulus, and swelling resistance were varied depend on the pre-treatment media utilized. Thermal properties of OPA-filled vulcanizates have been affected after CTAB and LENR modification, but the HCl pretreatment method showed no significant effect and behaves almost the same manner as raw OPA-filled vulcanizates. The CTAB, HCl, and LENR modification method also contribute the positive effect on retention properties of OPA-filled natural rubber vulcanizates after thermal ageing.